Pelatihan Membaca Puisi di MI Muhammadiyah Dukuhturi Bumiayu - Sigit Andi Prasetya; Lutfi Eskawati; Salsabila Fauziah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Poetry is part of the literary work taught to students in elementary school or madrasah ibtidaiyah, namely the ability to write and read poetry. Therefore, in order for students to have this ability, it is necessary to have the suitability and accuracy of strengthening the knowledge and abilities possessed by the teacher when poetry is taught. Writing poetry is directed at aspects of comprehension and at linguistic ability and suitability in implementing elements in poetry. Similarly, reading poetry leads to the ability to speak the written language of poetry by involving imagination, intonation, pronunciation, emphasis, and tone. The community service activity aims to provide poetry writing training for students at MI Muhammadiyah Dukuhturi Bumiayu. Service activities are carried out by the method of lectures, discussions, demonstrations, assignments, and mentoring. The steps of community service activities include the preparation stage, the implementation stage, and the evaluation stage. At the stage of implementing the service, it is carried out with 5 stages, namely (1) observation, (2) preparation of training and mentoring, (3) socialization of activities, (4) training and assistance in poetry writing training, and (5) evaluation. At the implementation stage, the implementation of student service activities is carried out in accordance with the activity schedule. The evaluation stage can be used as a benchmark for 85% success indicators and the implementation of activities. Based on the results of dedication, it is known that all students have high motivation and are able to write poems in accordance with intrinsic and extrinsic elements with the chosen poetry theme related to nature.